30-Day interbank futures: Investigating the process of price discovery following RBA cash target rate announcements - Smales, Lee (Elsevier BV * North-Holland, 2012)
The article examines microstructure issues in the Australian Interbank futures market by analyzing the price adjustment process following scheduled cash target rate announcements by the Reserve Bank of Australia. In characterizing the market response, three distinct stages of price formation and liquidity provision are identified. Market expectations around the RBA decision are derived explicitly from 30-Day Interbank futures. The first trade following the RBA decision occurs after 220 s on average, and after 234 s (1.73 trades) the market has adjusted to the theoretical settlement price. Deviations from theoretical prices post-announcement are common, particularly when a large amount of uncertainty exists around the RBA decision. The potentially costly issue of stale price quotes is also addressed.